Discrepancy between bulk-rock and zircon Hf isotopes accompanying Nd-Hf isotope decoupling. (15th August 2019) - Huang, Hui; Niu, Yaoling; Teng, Fang-Zhen; Wang, Shui-Jiong
Abstract: Zircon is an important accessory mineral for studying the crust-mantle interaction and crustal growth through time because zircon crystals not only allow precise dating but also record initial Hf isotope ratios of the host magma. Our study on a suite of gabbronorite, mafic diorite cumulate, diorite and granite from the Kekeli Batholith in the North Qilian Orogenic Belt, Northern Tibetan Plateau, shows (1) a significant Hf isotope discrepancy between zircon and their bulk rocks; and (2) bulk-rock Nd-Hf isotope decoupling. These observations thus demonstrate that zircons do not always capture the full history of magmatic system. The significant positive correlation between bulk-rock Hf isotope ratios and TiO2 content ( R 2 = 0.94) indicates that Ti-rich minerals (e.g., ilmenite, amphibole) are likely important Hf hosts. The early-formed Ti-rich minerals possibly record different Hf isotopes from those of zircons crystallized subsequently, thus causing discrepancy between zircon and bulk-rocks and leading to bulk-rock Nd-Hf isotope decoupling. Correlations between bulk-rock TiO2 content, Mg isotopes and Hf isotopes indicate a mixing process, with granite and gabbronorite representing two compositional endmembers. Because Ti minerals have higher crystallization temperatures than zircons, when the mixing melts have contrasting isotopes (or from heterogeneous sources/have a strong crustal contamination), the bulk-rock and zircon Hf isotope discrepancies reflect mineral crystallization sequence during mafic and felsic magma mixing. It is thus imperative to consider early formed minerals such as Ti-rich minerals and the bulk rock composition, not just zircons, when using Hf isotopes to track melt evolution and precisely constrain mantle contribution to granitoid petrogenesis.